Falsified Medicines Directive: Are We Heading in the Right Direction?. Issue 1 (2017) - Frontini, Roberto
Falsified medicines for human use are an increasing problem in Europe. The Falsified Medicines Directive (FMD) 2011/62/EU provides measures to prevent the entry of falsified medicines into the legal supply chain by requiring the placing of safety features consisting of a unique identifier (Ul) and an anti-tampering device (ATD). Some concerns have arisen from patients regarding the effectiveness of UI and ATD in terms of safety. In contrast, the relevance of the supply source as a key point for patients and pharmacists, especially in hospitals, has not been sufficiently considered by the FMD. Endorsing more Good Procurement Practices and Good Distribution Practices may be more effective. The implementation of the FMD in hospitals is wasting human resources and increasing costs, which will likely result in a poor positive outcome. At both European and national levels, it is now urgent to mitigate the consequences of the FMD by updating the legislation.